The Neurodegenerative Alzheimer’s Disease: A Critical Analysis - Krishna Babu Ojha; Ravi Rajput; Anurag; Soumyadip Mukherjee; Abhishek Kashyap; Yadav Rupali Vinod (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Researchers studied how dementia affects around 45 million people globally, according to estimates. Alzheimer’s disease (AD) is the leading cause of dementia, accounting for 60-80% of cases. It affects an estimated 5.8 million Americans aged 65 and more. In 2020, it is anticipated that payments for healthcare and hospice services for Americans 65 and older with dementia will total 305 billion. Physostigmine is an AChE inhibitor that was initially discovered from Calabar beans in 1864. Alzheimer’s disease (AD) is the leading cause of death in people aged 65 and older in the United States, according to a report by the Alzheimer’s Association. More than 90% of all patients experience restlessness, anxiety, depression, delusions, dementia, motor abnormality, irritability, sleep problems, hunger disorders, or poor impulse control. MicroRNAs, that influence gene expression post-transcriptionally, have been used to diagnose Alzheimer’s disease. Alzheimer’s disease is the most advanced type of dementia in the globe. The National Institute of Neurological Disorders and Stroke (NINCDS-ADRDA) has issued a new set of criteria for the diagnosis of Alzheimer’s disease. a\(β\) fragments and NFTs are significant markers for Alzheimer’s disease. Dementia, dependency, and disability all have social consequences. Alzheimer’s patients may benefit from drugs that help them maintain their freedom and optimize their functionality. These deposits arise as a result of native proteins folding incorrectly. Disinterest, anxiousness, nervousness, distress, delusions, dementia, motor activity abnormality, irritation, abnormal sleep problems, eating disorders, or poor impulse control affect Alzheimer’s patients. Alzheimer’s disease pathology may be slowed by the use of combination treatment and future tau pathology medicines. It is critical to diagnose AD early. Dementia can determine by an EEG test. The electric impulses of cortical neurons are read by EEG, which shows the function of the brain. AD can be treated with a variety of criteria, including programs, bodily fluids, and imaging studies. AchE inhibitors and many therapies are used for the treatment of AD. Gene therapy is a process that has a lot of attention in Studies. The basic method was to introduce a gene that produces an enzyme or growth factor that is reparative. Depending on the target ailment, the method of gene transfer and in-vivo vs ex-vivo treatment differs.